Sistem capaian berbilang terminal - Ismail, Ahmad (Penerbit UTM Press, 1990)
This paper describes a research on access method for the multi users system. The purpose is to enable an application system communicate with several other terminals simultaneously. The developed system is not restricted to synchronous terminals such as IBM 3270 or other compatible terminals but also to asynchronous terminals including microcomputers. The experiment is carried out on the IBM 4341 main frame, using the facilities at the Institute of Computer Science. The discussion is focussed on the approaches or methods that were adopted, design and system implementation.